Biological Activities of Soy Protein Hydrolysate Conjugated with Mannose and Allulose - Artorn Anuduang; Sakaewan Ounjaijean; Rewat Phongphisutthinant; Pornsiri Pitchakarn; Supakit Chaipoot; Sirinya Taya; Wason Parklak; Pairote Wiriyacharee; Kongsak Boonyapranai (Foods)
The non-enzymatic conjugation of peptides through the Maillard reaction has gained attention as an effective method to enhance biological functions. This study focuses on two conjugate mixtures: crude soy protein hydrolysate (SPH) conjugated with mannose (SPHM) and crude soy protein hydrolysate conjugated with allulose (SPHA). These two mixtures were products of the Maillard reaction, also known as non-enzymatic glycation. In vitro experiments were conducted to evaluate the antioxidant, anti-pancreatic lipase, inhibition of Bovine Serum Albumin (BSA) denaturation, and anti-angiotensin converting enzyme (ACE) activities of these conjugated mixtures. The results indicate that conjugated mixtures significantly enhance the antioxidant potential demonstrated via the DPPH and FRAP assays. SPHA exhibits superior DPPH scavenging activity (280.87 ± 16.39 µg Trolox/mL) and FRAP value (38.91 ± 0.02 mg Trolox/mL). Additionally, both conjugate mixtures, at a concentration of 10 mg/mL, enhance the BSA denaturation properties, with SPHM showing slightly higher effectiveness compared to SPHA (19.78 ± 2.26% and 5.95 ± 3.89%, respectively). SPHA also shows an improvement in pancreatic lipase inhibition (29.43 ± 1.94%) when compared to the SPHM (23.34 ± 3.75%). Furthermore, both the conjugated mixtures and rare sugars exhibit ACE inhibitory properties on their own, effectively reducing ACE activity. Notably, the ACE inhibitory effects of the individual compounds and their conjugate mixtures (SPHM and SPHA) are comparable to those of positive control (Enalapril). In conclusion, SPHM and SPHA demonstrate a variety of bioactive properties, suggesting their potential use in functional foods or as ingredients in supplementary products.